2021
DOI: 10.3390/math9050523
|View full text |Cite
|
Sign up to set email alerts
|

Oriented Fuzzy Numbers vs. Fuzzy Numbers

Abstract: A formal model of an imprecise number can be given as, inter alia, a fuzzy number or oriented fuzzy numbers. Are they formally equivalent models? Our main goal is to seek formal differences between fuzzy numbers and oriented fuzzy numbers. For this purpose, we examine algebraic structures composed of numerical spaces equipped with addition, dot multiplication, and subtraction determined in a usual way. We show that these structures are not isomorphic. It proves that oriented fuzzy numbers and fuzzy numbers are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

3
2

Authors

Journals

citations
Cited by 5 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…For example, price closes changes may be predicted with the use of prediction table presented in [125]. In [126], it is shown that OFN application for a portfolio analysis is more useful than the analogous application of FN. For these reasons, an imprecise PV may be evaluated by OFN [42,62].…”
Section: Oriented Fuzzy Present Valuementioning
confidence: 99%
See 1 more Smart Citation
“…For example, price closes changes may be predicted with the use of prediction table presented in [125]. In [126], it is shown that OFN application for a portfolio analysis is more useful than the analogous application of FN. For these reasons, an imprecise PV may be evaluated by OFN [42,62].…”
Section: Oriented Fuzzy Present Valuementioning
confidence: 99%
“…This replacement does not require any additional data. In [126], it is shown that oriented PV application for a portfolio analysis is more useful than the analogous application of fuzzy PV. This makes the use of O-BPV more preferred than the use of F-BPV.…”
mentioning
confidence: 99%
“…The notation I ≡ K means that "the interval I may be equivalently replaced by the interval K". The relationships between FNs, ordered FNs, and OFNs are discussed in detail in [34].…”
Section: Trapezoidal Oriented Fuzzy Numbers-basic Factsmentioning
confidence: 99%
“…Let symbol * denote any arithmetic operation defined in R and symbol * denote an extension of an arithmetic operation * to K [13]. Kosiński has defined arithmetic operators on ordered FNs in an intuitive way, but the addition of a dot product extended to the space K has a very high level of formal complexity [34]. Therefore, in many applications researchers limit their calculations to arithmetic operations determined in the space K Tr .…”
Section: Trapezoidal Oriented Fuzzy Numbers-basic Factsmentioning
confidence: 99%
See 1 more Smart Citation